After the Rain : how the West lost the East - Vaknin, Samuel, 1961-; Rangelovska, Lidija (Salt Lake City, UT : Project Gutenberg, 2003)
"After the Rain: How the West Lost the East" by Samuel Vaknin is a collection of provocative articles written in the late 20th century. The work examines how Western powers mishandled their foreign relations with Eastern Europe, particularly in the Balkans, resulting in a geopolitical and cultural rift. Vaknin critiques the interactions between Western ideologies and the complex realities of the East, detailing the economic failures, political corruption, and sociocultural dynamics that have characterized these transitional societies. At the start of the book, readers are introduced to the author's perspective, as he reflects on the reception of his prior writings. He notes the backlash from various groups, especially in the Balkans, who accuse him of racism while failing to recognize the socio-economic complexities at play. The early sections establish a dialogue about the state of these societies, discussing historical traumas and the pervasive corruption stemming from communist regimes. Vaknin's tone is critical and unflinching as he outlines the psychological and institutional decay resulting from both past regimes and contemporary Western influence, setting the stage for an in-depth exploration of the precarious balance between hope and despair in post-communist Eastern Europe. (This is an automatically generated summary.)
Release date is 2003-11-01
Keywords: Europe, Eastern -- Politics and government -- 1989-; Europe, Eastern -- Economic conditions -- 1989-